(3JaSjQ GjGJ GdGMcGe (B/s - (3GdUGHhfj, eMeO Ydjs ((3GdchjJ(B:s (3OGQ GdbQGf GdcQje,s, 1972)
(3JaSjQ NGU dGjGJ dGdGMcGe eSJeO ef GhKb eUGOQ GdJaSjQ GdbOjeI hGdMOjKI HGSdhH eHJcQ hWQjbI LOjOI eY YQV TGed ddCOdI GdabgGA hHjGf GdMceI GdJTQjYjI (B. s
Keywords: (3GdbQGfs -- (3JaSjQs